Discounting and Clustering in Seasoned Equity Offering Prices - Mola, Simona; Loughran, Tim (Journal of Financial and Quantitative Analysis, 2004)
Abstract An analysis of 4,814 SEOs during 1986–1999 indicates that the average offering ofnew shares is priced at a discount of 3% from the closing price on the day before the issue. Discounts have risen steadily over time, sharply increasing the indirect costs of issuing seasoned equity. There is evidence of increased clustering of offer prices at integers, and of greater importance in the analyst coverage provided by underwriters. Adjusting for other factors, we find that issues with integer offer prices, and underwriters with highly regarded analysts, are increasingly associated with larger discounts. The rise in discounts is consistent with an increased ability of investment bankers to extract rents from issuing firms.